2014
DOI: 10.1111/jdv.12420
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of dermal mesenchymal stem cells from patients with psoriasis

Abstract: These results indicate that MSCs from the derma of psoriasis patients might be involved in the early development of psoriasis because of their pro-angiogenic potential as well as the immunoregulatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 39 publications
6
65
0
Order By: Relevance
“…As reported in our previously published data (Hou et al, 2014), the cells cultured in this study were adherent, CD105 -, CD34 -, HLA -DR -, and presented a typical fibroblast flat triangular or spindle morphology, and could be induced to differentiate into both osteoblasts and adipocytes.…”
Section: Identification Of Cultured Dermal Mscssupporting
confidence: 48%
See 3 more Smart Citations
“…As reported in our previously published data (Hou et al, 2014), the cells cultured in this study were adherent, CD105 -, CD34 -, HLA -DR -, and presented a typical fibroblast flat triangular or spindle morphology, and could be induced to differentiate into both osteoblasts and adipocytes.…”
Section: Identification Of Cultured Dermal Mscssupporting
confidence: 48%
“…Although the exact mechanism of MSCs remains to be elucidated, soluble cytokines, such as TGF-b (Groh et al, 2005;Nemeth et al, 2010), IL-10 (Beyth et al, 2005), prostaglandin E2 (Aggarwal and Pittenger, 2005), nitric oxide (NO), and iNOS (Ren et al, 2008), are reportedly involved in these functions. In our previous study, we observed that inflammation and angiogenesisrelated genes, such as CXCL14,, and IGFBP5, were differentially expressed in dermal MSCs of patients with psoriasis (Hou et al, 2014). Therefore, researchers have attempted to identify the role of MSCs in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously investigated the biological characteristics and related gene expression patterns of bone marrow-derived MSCs in patients with psoriasis Hou et al, 2014). In addition to reduced proliferation activity and increased spontaneous apoptosis, bone marrow-derived MSCs in psoriasis were found to be associated with high expression of stem cell factor and granulocyte-colony stimulating factor, as well as low expression of inflammatory cytokines such as IL-1, IL-3, IL-18, and TNF-α.…”
Section: Introductionmentioning
confidence: 99%